Genetic Conservation of Brazilian Pine (Araucaria angustifolia) Through Traditional Land Use - Zechini A.A. (2018)
© 2018, The New York Botanical Garden.Traditional land use may play a key role in conserving and promoting ecosystem integrity. However, little is known about conserving genetic diversity in such traditional management systems. The Brazilian pine (Araucaria angustifolia) is an important element of traditionally managed landscapes in southern Brazil but is currently considered at risk of extinction. In order to assess the contribution of traditional management systems in conserving the Brazilian pine, we compared genetic diversity descriptors between traditionally used and protected populations. To accomplish this, we compared four managed populations against two protected populations in southern Brazil, using allozyme markers to estimate genetic indexes. All studied populations presented similar levels of genetic diversity and magnitude of outcrossing, indicating the potential for conserving the genetic diversity of A. angustifolia populations in traditionally managed land use systems. Traditional management systems should be considered in conservation strategies for Araucaria Forest because they help maintaining the genetic diversity of keystone species, while keeping cultural practices alive.